2016
DOI: 10.1111/and.12620
|View full text |Cite
|
Sign up to set email alerts
|

Age is a significant predictor of early and late improvement in semen parameters after microsurgical varicocele repair

Abstract: Accumulating evidence indicates that varicocele repair improves sperm quality. However, longitudinal changes in sperm parameters and predictors of improved semen characteristics after surgery have not been fully investigated. We retrospectively reviewed data from 100 men who underwent microsurgical subinguinal varicocele repair at a single centre. Follow-up semen examinations were carried out at 3, 6 and 12 months post-operatively. Logistic regression was used to identify predictors of early (3 months) and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
(18 reference statements)
3
9
0
Order By: Relevance
“…[ 27 ] A study showed that younger age was associated with better improvements in total motile sperm counts after microsurgical varicocele repair compared with older men. [ 20 ] In the present study, age was independently associated with semen volume, motility, and total sperm count. Discrepancies among the present study and previous ones [ 25 27 ] could be due to a number of factors, including population, genetics, stress, and diet.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…[ 27 ] A study showed that younger age was associated with better improvements in total motile sperm counts after microsurgical varicocele repair compared with older men. [ 20 ] In the present study, age was independently associated with semen volume, motility, and total sperm count. Discrepancies among the present study and previous ones [ 25 27 ] could be due to a number of factors, including population, genetics, stress, and diet.…”
Section: Discussionsupporting
confidence: 50%
“…[ 16 ] Supporting the association between varicoceles and infertility, surgical repair of varicoceles has been shown to increase sperm concentration and to improve sperm motility. [ 20 24 ] A recent meta-analysis showed that varicocele repair improves sperm parameters, probably by reducing sperm oxidative stress and DNA damage. [ 9 ] All types of repair improve these parameters, but microsurgical repair seems to produce the best outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…19 Of interest, Kimura and colleagues revealed that patients younger than 37 years old experienced greater early (3 months) and late (⩾6 months) improvements in semen parameters after microsurgical varicocele repair, however, they did not exclude the possibility of semen parameter improvement in older men, and concluded that microsurgical varicocele repair could also be beneficial for older men. 20 The main problem concerning investigations on how much age can influence seminal parameters and their possible improvement after a treatment lies in the fact that the patient's age at the time of varicocele diagnosis is not related to the onset of the disease but is related to the patient's desire for children, this may represent a huge bias with no solution. In this context, what is of clinical importance is the effective improvement of the seminal parameters of these patients following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, current evidence indicates that the degree of improvement in semen parameters 3 months after varicocelectomy remains the same, or stable, 12 months after surgery. [20][21][22][23][24][25][26][27][28][29][30][31][32] In addition, no comparison with other varicocelectomy techniques was performed, with microsurgical varicocele repair being the gold standard in varicocele treatment. 7 Another limitation of the current study is its retrospective design for which we did not have data collection with standardized protocols regarding the hormonal profiles of the patients, therefore, making any speculation impossible.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kimura et al. (2017) noted that younger age (<37 years) was associated with early and late post‐operative improvement in TMSC. Conversely, Palmisano et al.…”
Section: Discussionmentioning
confidence: 91%